ANALISIS YURIDIS TERHADAP TINDAK PIDANA PENGANIAYAAN YANG MENGAKIBATKAN KORBAN LUKA BERAT - Rangga Fahbri Haryanata; M Sifa Fauzi Yulianis (INTELIGENSIA MEDIA, 2024)
The purpose of this study is to discuss and analyze the application of material criminal law to the criminal act of persecution that results in serious injury to the victim and discuss and analyze the supporting and inhibiting factors in the application of material criminal law to the criminal act of persecution that results in serious injury to the victim. Research includes normative legal research. The results showed that: a) The application of material criminal law to the criminal act of maltreatment resulting in serious injury to the victim, namely referring to Article 354 of the Criminal Code which indicates that whoever intentionally seriously injures another person, is threatened with severe maltreatment with a maximum imprisonment of eight years; and b) Supporting factors in the application of material criminal law to criminal acts of persecution that result in serious injury to victims, namely the existence of regulations governing the settlement of criminal acts and the existence of a clear legal basis. If there is no legal basis governing the settlement of crimes in the police, the police will not resolve the crime of maltreatment resulting in serious injury to the victim will be forwarded to the court. Meanwhile, the inhibiting factor in the application of material criminal law to the criminal act of persecution that results in serious injury to the victim is the ever- changing mode of the perpetrator and the silence carried out by the suspect.